Hippocampal subfields and decline in activities of daily living in Alzheimer’s disease and dementia with Lewy bodies (2020)
Background: Hippocampal atrophy is presented in Alzheimer’s disease (AD) and dementia with Lewy bodies (DLB). Cognition, dual-tasks, muscular function, goal-related behaviors and neuropsychiatric symptoms are linked to hippocampal volumes and may lead to functional decline in activities of daily living. We examined the association between baseline hippocampal subfield volumes (HSv) in mild AD and DLB, and functional decline. Materials & methods: 12 HSv were computed from structural magnetic resonance images using Freesurfer 6.0 segmentation. Functional decline was assessed using the rapid disability rating scale score. Linear regressions were conducted. Results: In AD, HSv were smaller bilaterally. However, HSv were not associated with functional decline. Conclusion: Functional decline does not depend on HSv in mild AD and DLB